Role of the external drivers in the occurrence of low-latitude ionospheric scintillation revealed by multi-scale analysis - Spogli, Luca (2019)
We analyze the amplitude scintillation on L-band signals over San Miguel de Tucumán (Argentina), focusing on the multi-scale variability and speculating on the possible relationship between forcing factors from the geospace and the ionospheric response. The site is nominally located below the expected position of the southern crest of the Equatorial Ionospheric Anomaly (EIA). For this scope, we concentrate on the period 1?31 March 2011, during which one minor and one moderate storm characterize the first half of the month, while generally quiet conditions of the geospace stand for the second half. By leveraging on the Adaptive Local Iterative Filtering (ALIF) signal decomposition technique, weinvestigate the multi-scale properties of Global Navigation Satellite Systems (GNSS) amplitude scintillation and helio-geophysical parameters, looking for possible cause-effect mechanisms relating the former to the latter. Namely, we identify resonant modes in the Akasofu (e) parameter as likely related to the frequency components in the time evolution found for the amplitude scintillation index, hence modulating the scintillation itself.